Efektivitas Mulsa Organik dan POC Limbah Rumah Tangga terhadap Pertumbuhan dan Hasil Umbi Kentang Kuning (Solanum tuberosum L) di Curup - Adnan Adnan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Adnan A. 2019. Effectiveness of organic mulch and household waste poc against growth and yield of yellow potato bulb (Solanum tuberosum L) in Curup. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 305-317. Palembang: Unsri Press. The study was conducted mid-June 2018 to December 2018, in the Air Rambai Village, Curup Tengah District, Rejang Lebong District. At an altitude of 600 m above sea level. Liquid organisms (POC) fertilizers can be utilized directly by plants, environmentally friendly, economically household waste materials are easily available and can be used in the process of making raw materials for liquid fertilizer. mulch as ground cover in maintaining soil moisture, reducing weeds, direct sunlight that affects roots and potato tubers. POC and organic mulch are natural resources as raw materials are easily obtained in Rejang Lebong Regency. Factorial Randomized Group Design, ie organic mulch (M), M1 = No mulch, M2 = banana leaf, M3 = rice husk, M4 = coffee husk. POC (O), namely: O0 = No poc, O1 = poc 50 ml/liter of water, O2 = poc 75 ml/liter of water and O3 = poc 100 ml / liter of water. Amount of 288 potato seeds. The results of variance of poc (O) and mulch (M) have a very significant effect on variables: number of main stems, number of shoots, wet weight, and stem diameter. Furthermore, the combination treatment of coffee with a dose of 50 ml/l of liquid fertilizer up to 75 ml/l of water has a very significant effect on the variables: number of main stems, plant height, number of shoots, wet weight and tuber diameter. The combination treatment of rice scoop mulch and liquid fertilizer 100 ml/ l of water is there interaction with wet weight and tuber diameter Both treatments (there are interactions with variables: plant height, number of main stems, number of shoots, wet weight and tuber diameter).Conclusion: The use of rice scoop mulch can increase wet weight and tuber tuber diameter, POC 75 ml/l water to the number of shoots, tuber wet weight. The combination of coffee scaffolding mulch with a dose of poc 50-75 ml/l of water has an effect on the growth of plant height, number of shoots and main stems. Combination of rice scam mulch and 100 ml/l poc of water there is interaction with wet weight and tuber diameter.Keywords: liquid fertilizer, mulch, potatoes